An autoethnographic perspective on the broadening of missiological perspectives in teaching mission in Anglican TEIs in England. Issue 4 (October 2018) - Worsley, Howard
This is a reflection on how attitudes to mission in England have changed during the last half century. It offers a comparison between a pre-adolescent's and an adult theological educator's understanding of Anglican mission seen through the lens of Robinson Crusoe . Defoe's foundational novel Robinson Crusoe is used as the launch point by using the author's personal experience as he rereads this childhood favorite alongside his wider sociological study of missiological perspectives. Beginning with the personal perspective of a child growing up in England in the 1960s, developmental, societal, and sectarian influences are considered as ways in which the author's individualized outlook on world mission was initially shaped as a child. Second, a wider lens is used to look at how anthropological and general ecclesiological outlooks have served to broaden the author's adult understanding of mission in the context of an Anglican TEI.